Central Europe - Richard Robinson (Europe in British Literature and Culture, 2024)
This chapter answers the question ’does central Europe exist?’ by first drawing a literary-historical line between Franz Kafka and Milan Kundera, focusing particularly on the critical tensions in Kundera’s construction of a vanished culture and on the West’s mythologizing of central Europe. It then turns to two Prague-set novels, Bruce Chatwin’s Utz, which explores the condition of stubborn aesthetic individualism under communism, and Tom McCarthy’s Men in Space, set in the months following the splitting-up of Czechoslovakia in 1992. Beyond the Czech lands, the Austrian Ingeborg Bachmann’s Malina, a significant work of avant-garde feminism, offers a doomed fantasy of post-war Austro-Hungarian relationships. Olga Tokarczuk’s Drive Your Plow over the Bones of the Dead, set in the Polish–Silesian borderlands, is a revenge thriller whose narrator is inspired by the radicalism of William Blake. These case studies signal the ways central Europe has been confabulated by British writers; they also show how an evolving canon of fiction-in-translation is appropriately pluralizing and updating the West’s idea of the ‘middle’.